The Effectiveness of OBE Worksheets in Improving Student Learning Outcomes in Educational Psychology Courses - Nurhafsari Putri, Utami; Sri Milfayetty; Nani Barorah Nasution; Suri Handayani; Nuraini (Universitas Negeri Medan, 2025)
This study examines the effectiveness of structured OBE worksheets (LK) on the learning outcomes of students in the Educational Psychology course at the State University of Medan (UNIMED) in the 2024 academic year. A quasi-experimental design was applied by comparing two groups of students: those who used worksheets (N = 78) and those who did not (N = 78). The worksheet group consisted of students from the Mechanical Engineering Education classes A, B, and C, while the non-worksheet group included students from the Building Engineering Education classes A and C, and the Automotive Engineering Education class B. Final exam scores were analyzed using an independent samples t-test. The results showed a significant difference between the groups, with the worksheet group achieving a higher average score (M = 51.31) than the non-worksheet group (M = 45.87; t = 2.50, p = 0.014, p < 0.05), indicating a positive impact on conceptual understanding and academic performance. Additionally, data were collected from 670 students and 13 lecturers teaching Educational Psychology at UNIMED through closed and open-ended questionnaires. Descriptive analysis revealed that the majority of students (76.7%) and lecturers (77%) preferred printed worksheets. Students rated the visual appearance of the worksheets, outcome-based focus, clarity of language, and content as good, while faculty members valued the comprehensive structure, innovative teaching approach, and relevance to students' future professional needs. These results indicate the effectiveness of worksheets not only in cognitive outcomes but also in enhancing satisfaction and engagement. This study highlights the importance of integrating structured worksheets into pedagogical practices, particularly in technical education, to support holistic student development.